Combustion synthesis of NbC/ZrO2 composites: Influence of Cr additives on the microstructure and mechanical properties. Issue 5 (16th June 2021) - Zaki, Zaki I.; Al‐qahtani, Mohsen; Alotaibi, Saad H.; El‐Sadek, Mohamed H.; Ahmed, Hesham; Ahmed, Yasser M. Z.
Abstract: Composites of NbC/ZrO2  reinforced with different weight ratios of Cr metal were prepared by dynamic compaction combustion from a blend of Nb2 O5 –Zr–Cr powders. Factors controlling the synthesis process, the microstructure, and the mechanical properties of the samples, such as Cr wt% and the compression loads were studied. The samples were characterized by XRD, SEM, porosity, and hardness measurements. The porosity value of the sample with no additives was high and reached 31.6 vol%. A sudden decrease in the sample porosity to 2.4 vol % was noticed for the sample containing 3.0 wt% of Cr. A high‐density sample with less than 2.0 vol % porosity and maximum hardness of 1038 HV was produced using 5.0 wt% Cr under 300 MPa compression load. Detailed thermodynamic calculations for the effect of Cr additives on the physicochemical properties of the system were introduced.